1992
DOI: 10.1093/protein/5.6.559
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of disuiphide bridge function in recombinant bovine prolactin using site-specific mutagenesis and renaturation under mild alkaline conditions: a crucial role for the central disuiphide bridge in the mitogenic activity of the hormone

Abstract: We have previously described a method for isolating Escherichia coli-produced methionyl bovine prolactin (Met-bPRL) and its renaturation using thioredoxin. This report describes an alternative renaturation procedure in which extracted Met-bPRL is incubated in air at pH 10 and 20 degrees C. Within 1 h of such treatment essentially all of the reduced Met-bPRL was converted to the oxidized form; this was accompanied by an increase to full mitogenic activity in the Nb2 cell bioassay. It was also found that, to min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The assay is also useful for the analysis of structure-function relationships of lactogenic hormones [35]. The proliferative activities of lactogenic hormones for Nb2 cells are mediated by cell surface PRL-R [36].…”
mentioning
confidence: 99%
“…The assay is also useful for the analysis of structure-function relationships of lactogenic hormones [35]. The proliferative activities of lactogenic hormones for Nb2 cells are mediated by cell surface PRL-R [36].…”
mentioning
confidence: 99%
“…In mammals, the "up-up-down-down" topography of helix H1-H4 in PRL is a typical feature of the members of GH/PRL family (Brooks, 2012). Besides, the disulfide bonds formed by conserved pairs of Cys residues not only play a role in maintaining the 3D protein structure but also contribute to the bioactivity of PRL, e.g., the mitogenic activity in NB2 cells (Luck et al, 1992) and osmoregulatory ability in urinary bladder (Doneen et al, 1979). Using in situ hybridization with riboprobe based on the PRL sequence obtained, PRL transcript expression was mapped to the RPD of the carp pituitary and overlapped with the distribution of lactotrophs with PRL immunoreactivity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been reported that cysteine to serine substitutions can lead to increased solubility of recombinant proteins (Luck et al, 1992), the two cysteine residues not included in the predicted essential loop formation were substituted for serine residues. A synthetic gene fragment encoding this peptide was assembled as described above and denoted GCys (Fig.…”
Section: Design Of G-protein Gene Fragments and Construction Of Gene mentioning
confidence: 99%
“…Rinas et al (1992) showed that a single cysteine residue substitution caused a dramatic decrease in solubility, while two other cysteine to serine substitutions did not alter the solubility properties. In contrast, Luck et al (1992) demonstrated that by replacing cysteine residues with serine residues in bovine prolactin, a significant increase in the protein solubility was achieved. Furthermore, Hellebust et al (1989) showed that the replacement of basic amino acids in a recombinant protein can dramatically enhance the proteolytic stability in vivo.…”
mentioning
confidence: 94%
See 1 more Smart Citation